Dynamically changing extracellular matrix stiffness drives Schwann cell phenotype - Alyssa Montgomery; Jennifer Westphal; Andrew E. Bryan; Greg M. Harris (Matrix Biology Plus, 2025)
Schwann cells (SCs) hold key roles in axonal function and maintenance in the peripheral nervous system (PNS) and are a critical component to the regeneration process following trauma. Following PNS trauma, SCs respond to both physical and chemical signals to modify phenotype and assist in the regeneration of damaged axons and extracellular matrix (ECM). There is currently a lack of knowledge regarding the SC response to dynamic, temporal changes in the ECM brought on by swelling and the development of scar tissue as part of the body’s wound-healing process. Thus, this work seeks to utilize a biocompatible, mechanically tunable biomaterial to mimic changes in the microenvironment following injury and over time. Previously, we have reported that ECM cues such as ligand type and substrate stiffness impact SC phenotype and plasticity, which was demonstrated by SCs on mechanically stable biomaterials. However, to better realize SC potential for plasticity following traumatic injury, a UV-tunable polydimethylsiloxane (PDMS) substrate with dynamically changing stiffness was utilized to mimic changes over time in the microenvironment. The dynamic biomaterial showed an increase in stress fibers, greater YAP expression, and fluctuations in c-Jun production in SCs in comparison to stiff and soft static controls. Utilizing biomaterials to better understand the role between temporal mechanical dynamics and SC phenotype holds a very high potential for developing future PNS therapies.